2006
DOI: 10.1017/s002531540601321x
|View full text |Cite
|
Sign up to set email alerts
|

A complex sexual cycle in sandy beaches: the reproductive strategy of Emerita brasiliensis (Decapoda: Anomura)

Abstract: Reproductive tactics displayed by the mole crab Emerita brasiliensis that inhabits Atlantic beaches of South America are reported. The analysis of external sexual characters and reproductive organs disclosed seven developmental forms: megalopae, neotenic males, early females, juveniles, males, females (ovigerous or not) and intersex individuals. Precocious acquisition of gonopores in females, production of spermatophores in neotenic males and presence of juveniles and intersex individuals are reported for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
7
1
2
Order By: Relevance
“…Larvae are released in the intertidal zone and although highest concentrations of Stage I were found close to shore, high offshore advection was evident even for this first stage. The annual bimodal spawning pattern of E. analoga in late summer (this study) and also in winter (Contreras et al 1999) differs from the unimodal pattern of larval release of E. brasiliensis from the Atlantic coast at approximately the same latitude (Delgado & Defeo, 2006). Since closely related species from the same habitat tend to develop convergent strategies when faced to similar environmental pressures, we proposed that the oceanographic setting (seasonal upwelling dynamics) in south central Chile influences the timing of E. analoga larval release.…”
Section: Larval Distribution and Species Ecologycontrasting
confidence: 49%
“…Larvae are released in the intertidal zone and although highest concentrations of Stage I were found close to shore, high offshore advection was evident even for this first stage. The annual bimodal spawning pattern of E. analoga in late summer (this study) and also in winter (Contreras et al 1999) differs from the unimodal pattern of larval release of E. brasiliensis from the Atlantic coast at approximately the same latitude (Delgado & Defeo, 2006). Since closely related species from the same habitat tend to develop convergent strategies when faced to similar environmental pressures, we proposed that the oceanographic setting (seasonal upwelling dynamics) in south central Chile influences the timing of E. analoga larval release.…”
Section: Larval Distribution and Species Ecologycontrasting
confidence: 49%
“…For example, there is paedomorphic plasticity in the carapace hingements and inner marginal carapace area of ostracods (Ozawa and Ishii 2008). Similar to the kind of heterochrony that may be occurring in P. monodon, some other species of Crustacea show variations in the timing of appearance and rates of character development, which occur at different stages in abbreviated larval development, such as euphausiids, brachyurans, and anomurans (Makarov and Maslennikov 1981;Clark 2005;Delgado and Defeo 2006). Particularly for the anomuran mole crab, Emerita brasiliensis, Delgado and Defeo (2006) state ''The principal benefit to early maturation is demographic: sexually mature neotenic males are most likely to succeed since they have less chance of dying before maturation.''…”
Section: Discussionmentioning
confidence: 99%
“…Heterochronic phenotypic variation has been reported for several species. For crustaceans it has been associated with an abbreviated larval development (Makarov and Maslennikov 1981;Clark 2005;Delgado and Defeo 2006;Kavanagh et al 2006;Ozawa and Ishii 2008). In some species, heterochronic plasticity translates into the existence of more than one form of adult, but without genetic differentiation between forms.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate larval stages increase offshore distance, and approach the coast again during later planktonic stages (Veloso & Valentin 1993). The sedentary phase includes juveniles, which are derived from the megalopa stage that settles on to the beach, and different developmental stages leading to adulthood (Delgado & Defeo 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate larval stages increase offshore distance, and approach the coast again during later planktonic stages (Veloso & Valentin 1993). The sedentary phase includes juveniles, which are derived from the megalopa stage that settles on to the beach, and different developmental stages leading to adulthood (Delgado & Defeo 2006.Preliminary observations showed that the species also inhabits estuarine beaches affected by the estuarine gradient generated by the Rio de la Plata. However, the simultaneous role of morphodynamics and estuarine gradients in modeling large-scale demographic patterns has not been assessed.…”
mentioning
confidence: 96%